On the strength and interfacial properties of square wave joints with defects and mismatches. Issue 13 (3rd October 2021) - Guo, Wang; Chen, Peijian; Liu, Hao; Yang, Yugui; Peng, Guangjian; Chen, Zhitong
ABSTRACT: In the present paper, the strength and interfacial properties of square-wave joints under tension are analyzed. By using the bilinear cohesive zone model, three main factors in practice, including geometric parameters, preexisting defects and mismatches, are considered. It is found that the strength and fracture toughness of the joints can be improved by proper adjustment of geometric parameters of the joint. What is more, the length of defect has a great influence on the mechanical properties of the adhesive joints, different from the defect's location. Compacting adherends tightly during glue consolidation, making the bonding part as symmetrical as possible and introducing some protuberances on square-wave plug are found to be helpful to improve the joints' mechanical behavior. The findings should be useful for the design of square-wave joints and the assessment of mechanical properties of adhesive joints in practical and potential applications.